2014
DOI: 10.5012/bkcs.2014.35.5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of 4-Methylbenzenethiol Self-Assembled Monolayers on Au(111) by Scanning Tunneling Microscopy

Abstract: Self-assembled Monolayers (SAMs) Formed by the Spontaneous Adsorption of Organic Thiols on Metal Surfaces offer a powerful route for potential applications in a variety of fields such as corrosion inhibition, lubrication, sensors, biointerface, and nanopatterning. [1][2][3][4] Recently, SAMs of aromatic thiols have drawn considerable attention due to their practical applications in molecular electronic devices. 5,6 It has been demonstrated that the work function of metal electrodes in electronic devices can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On the other hand, the steric effect of the −NO 2 group on NBT is minimized because it is in a planar structure with the phenyl ring. Finally, aromatic thiols with multiple phenyl rings are reported to pack more efficiently compared to aromatic thiols with a single phenyl ring. ,, Therefore, we infer that the observed energy trend could be explained by the effect of molecular structure on π–π stacking. MTP with the bulky methyl group has relative low efficiency in redistributing its energy to surrounding molecules, which leads to higher energy and an extended lifetime of the deposited energy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the steric effect of the −NO 2 group on NBT is minimized because it is in a planar structure with the phenyl ring. Finally, aromatic thiols with multiple phenyl rings are reported to pack more efficiently compared to aromatic thiols with a single phenyl ring. ,, Therefore, we infer that the observed energy trend could be explained by the effect of molecular structure on π–π stacking. MTP with the bulky methyl group has relative low efficiency in redistributing its energy to surrounding molecules, which leads to higher energy and an extended lifetime of the deposited energy.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Although the exact adsorption geometry depends on molecule surface coverage and preparation condition, previous studies have showed that the orientation of densely packed aromatic thiols are nearly upright, with a tilt angle of ∼20°−30°to the surface normal. [27][28][29]39 In this study, we used excessive amounts of aromatic thiols to achieve full surface coverage, so the molecules can be considered densely packed on the surface. While the surfaces used here are highly heterogeneous, the orientation of the dipole relative to the metal surface is most likely similar for the range of molecules studied due to the similarities in structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption of thiols onto metals creates self‐assembled monolayers (SAMs) that can provide a versatile route for fabrication of nanoscale structures and functionalized monomolecular thin films . Two‐component mixed SAMs are especially promising due to their strong potential to tune the physical and chemical properties of surfaces by changing the tail group, length, and chemical structure of the thiol molecular backbone.…”
Section: Acknowledgmentsmentioning
confidence: 99%